ANALISIS KEBIJAKAN PEMERINTAH TERKAIT PENGATURAN HARGA TIKET PESAWAT DI INDONESIA - Mailinda Eka Yuniza; muhammad Jibril; Aicha Grade Rebecca (WARTA ARDHIA, 2020)
Deregulation made by Government Regulation No. 40 of 1995 has intensified the competition in the aviation industry. As time passes by, many airlines implement the Low-Cost Carrier (LCC) concept. The negative effect of these LCC is that aviation companies compete to lower their prices, thus neglecting the safety factor. This research method employed in this research is normative research, whereas the material used is secondary data. The result of this research indicates that airplane ticket prices, especially economy class, are regulated in Ministry of Transportation Decree Number KM 106 of 2019 about The Upper Limit Tariff for Passengers in Economy Class Services for Scheduled Domestic Commercial Air Transport. On the other hand, this ministerial decree has not been able to solve the issues that arise in our society. Authors think that airplane ticket price as one of the essential production branches for the country needs to regulated thoroughly in order to achieve the greatest prosperity of the people in accordance with Article 33 of the 1945 Constitution.